Use and potential of nanotechnology in cosmetic dermatology - Pierfrancesco Morganti (Dove Medical Press, 2010)
Pierfrancesco MorgantiDepartment of Dermatology and Venereal Diseases, II University of Naples, Naples, ItalyAbstract: Biotechnology and nanotechnology are the key technologies of the twenty-first century, having enormous potential for innovation and growth. The academic and industrial goals for these technologies are the development of nanoscale biomolecular substances and analytical instruments for investigating cell biology at the cellular and molecular levels. Developments in nanotechnology will provide opportunities for cosmetic dermatology to develop new biocompatible and biodegradable therapeutics, delivery systems and more active compounds. Cosmetics have the primary function of keeping up a good appearance, changing the appearance, or correcting body odors, while maintaining the skin and its surroundings in good conditions. Thus cosmetic dermatology, recognizing the new realities of skin care products, has to emphasize the functional aspects of cosmetics through an understanding of their efficacy and safety in promoting good health. Nanoscience may help the scientific community to find more innovative and efficacious cosmetics. Understanding the physical model of the cell as a machine is essential to understand how all the cell components work together to accomplish a task. The efficacy and safety of new nanomaterials has to be deeply studied by ex vivo tests and innovative laboratory techniques. New delivery systems and natural nanocompounds, such as chitin nanofibrils for wound healing, are being used in cosmetic dermatology with good results, as are nanostructured TiO2 and ZnO sunscreens. The challenge is open.Keywords: nanotechnology, nanobiotechnology, delivery systems, chitin nanofibrils, TiO2, ZnO